COMMUNICATING THE SEVERE DIAGNOSIS – PSYCHOLOGICAL, ETHICAL AND LEGAL ASPECTS - Andrada PÂRVU; Adina REBELEANU; Anca BOJAN (Studia Universitatis Babeș-Bolyai. Philosophia)
From a psychological standpoint, communicating a severe diagnosis entails more than just naming a disease, it is a complex process with a number of stages: finding out what the patient already knows about the illness (some of which might be wrong, and thus psychologically detrimental), informing the patient while answering any questions (about the illness itself, the treatment, prognosis, recovery period, etc.) and last but not least, providing a minimum of psychological support depending on the patient’s reaction. Romanian law regarding doctor-patient relationship and communication is modeled on the Anglo-Saxon model centered on patient autonomy and direct communication with the latter if the patient desires to know the truth about his condition. If this is not the case, the patient can name a proxy for doctor-patient communication. There are three legal documents that clarify these aspects: Law of Patient Rights, Medical Association’s Ethics Code and the Health Reform Law. The first two are conflicting on several aspects that we will discuss in this paper. The few studies on doctor-patient communication published in Romania reveal that there is no unitary methodology in this field. The doctors attest that often times the patient’s family, when faced with severe illness turn to the traditional model of communication, i.e. they desire to know the severe diagnosis first and pressure the physician to hide the truth form the patient, contrary to the letter of the law. The aim of this paper is to discuss the issue of communicating severe diagnosis in nowadays Romania in a very complex context: 1. The model of doctor-patient relationship and communication has changed after communist era (from paternalistic to partenerial); 2. Conflicting and missing issues in laws; 3. Laws based on patient’s autonomy principle in a traditional society based on another model of taking care (the patient is part of a family nucleus and the family wants to interfere into the medical communication process). Communication has only recently entered the curriculum of some medical schools in Romania. The doctors questioned as part of a study reveal that they‘ve learned to communicate a severe diagnosis by trial and error. This being said we recommend the inception of practical doctor-patient communication courses that could lead to improving doctor-patient relationships, communication of the diagnosis being their foundations.